2016
DOI: 10.1007/s00426-016-0744-7
|View full text |Cite
|
Sign up to set email alerts
|

Let it go: the flexible engagement and disengagement of monitoring processes in a non-focal prospective memory task

Abstract: Remembering to perform a delayed intention is referred to as prospective memory (PM). In two studies, participants performed an Eriksen flanker task with an embedded PM task (they had to remember to press F1 if a pre-specified cue appeared). In study 1, participants performed a flanker task with either a concurrent PM task or a delayed PM task (instructed to carry out the intention in a later different task). In the delayed PM condition, the PM cues appeared unexpectedly early and we examined whether attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In line with this, our findings suggest that focality primarily impacts the allocation of strategic resources to the task (top-down processes), namely, a higher investment of resources to monitor the environment for the target cue in nonfocal (compared to focal) tasks Scullin, McDaniel, Shelton, et al, 2010). This flexible investment of attentional resources in response to particular task characteristics (such as focality affecting ongoing task measures in the present study) has similarly been shown when importance of the PM task was enhanced (Hering et al, 2014;Kliegel et al, 2001;Kliegel, Martin, et al, 2004) or when information about the relevant context for the PM task was provided (Cohen et al, 2016;Kuhlmann & Rummel, 2014;Marsh et al, 2006).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In line with this, our findings suggest that focality primarily impacts the allocation of strategic resources to the task (top-down processes), namely, a higher investment of resources to monitor the environment for the target cue in nonfocal (compared to focal) tasks Scullin, McDaniel, Shelton, et al, 2010). This flexible investment of attentional resources in response to particular task characteristics (such as focality affecting ongoing task measures in the present study) has similarly been shown when importance of the PM task was enhanced (Hering et al, 2014;Kliegel et al, 2001;Kliegel, Martin, et al, 2004) or when information about the relevant context for the PM task was provided (Cohen et al, 2016;Kuhlmann & Rummel, 2014;Marsh et al, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…The costs of adding a PM task to an ongoing task were calculated by subtracting each participant's mean response time in the ongoing-task-only block from the mean response time of the ongoing task trials in each PM block. Following previous research, response times of incorrect ongoing task trials, of PM trials, and of the two trials following each target cue, were omitted from analyses (for similar procedure, see Boywitt & Rummel, 2012;Brewer, 2011;Cohen et al, 2016;Horn, Bayen, & Smith, 2013). A mixed-factorial ANOVA indicated significant main effects of maintenance load, F(1, 163) = 26.95, p < .001, η p 2 = .14, focality, F(1, 163) = 5.82, p = .02, η p 2 = .03, and age, F(1, 163) = 10.24, p < .01, η p 2 = .06, reflecting higher ongoing task response time costs in the highcompared to the low-maintenance load condition, nonfocal tasks compared to focal tasks and higher costs for older adults as compared with younger adults.…”
Section: Ongoing Task Response Time Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic multiprocess view (DMPV) (Scullin et al, 2013; Shelton and Scullin, 2017) proposes that people have a flexible choice between proactive control and reactive control that primarily depends on the contextual likelihood of a PM event. According to this model, individuals will rely on reactive control when the probability of a PM event is low, and then abruptly “switch on” proactive control when an environmental cue signals an increased likelihood of a PM event (Kuhlmann and Rummel, 2014; Ball et al, 2015; Cohen et al, 2017). However, previous work has primarily relied on blocked experiment designs or taken an all-or-none approach to measuring PM strategy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent update of dual-process PM theory, the dynamic multiprocess framework (DMPV 51,52 ), proposes that people have a flexible choice between proactive control and reactive control that primarily depends on the contextual likelihood of a PM event. According to this model, individuals will rely on reactive control when the probability of a PM event is low, but then temporarily "switch on" proactive control when a cue in the environment signals an increased likelihood of the PM event (in support of this theory see [53][54][55] ). While DMPV hypothesizes a fluid relationship between proactive and reactive control modes, this relationship has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%